Cybersecurity law - Kosseff, Jeff 1978- (Hoboken Wiley, 2023)
"Cybersecurity is the process of applying security measures to ensure confidentiality, integrity, and availability of data. The goal of cybersecurity is to protect assets, which includes data, desktops, servers, buildings, and most importantly, humans"
Data security laws and enforcement actions-- Cybersecurity litigation-- Cybersecurity requirements for specific industries-- Cybersecurity and corporate governance-- Antihacking laws-- U.S. government cyber structure and public-private cybersecurity partnerships-- Surveillance and cyber-- Cybersecurity and federal government contractors-- Privacy laws-- International cybersecurity law-- Cyber and the law of war-- Ransomware.
Includes bibliographical references and index.
Keywords: Computer security -- Law and legislation -- United States; Data protection -- Law and legislation -- United States